The 1.5 Ms observing campaign on IRAS 13224−3809 – I. X-ray spectral analysis. Issue 3 (30th March 2018) - Jiang(姜嘉陈), J; Parker, M L; Fabian, A C; Alston, W N; Buisson, D J K; Cackett, E M; Chiang, C-Y; Dauser, T; Gallo, L C; García, J A; Harrison, F A; Lohfink, A M; et al.
Abstract: We present a detailed spectral analysis of the recent 1.5 Ms XMM–Newton observing campaign on the narrow-line Seyfert 1 galaxy IRAS 13224−3809, taken simultaneously with 500 ks of NuSTAR data. The X-ray light curve shows three flux peaks, registering at about 100 times the minimum flux seen during the campaign, and rapid variability with a time-scale of kiloseconds. The spectra are well fit with a primary power-law continuum, two relativistic-blurred reflection components from the inner accretion disc with very high iron abundance, and a simple blackbody-shaped model for the remaining soft excess. The spectral variability is dominated by the power-law continuum from a corona region within a few gravitational radii from the black hole. Additionally, blueshifted Ne x, Mg xii, Si xiv, and S xvi absorption lines are identified in the stacked low-flux spectrum, confirming the presence of a highly ionized outflow with velocity up to v = 0.267 and 0.225 c. We fit the absorption features with xstar models and find a relatively constant velocity outflow through the whole observation. Finally, we replace the bbody and supersolar abundance reflection models by fitting the soft excess successfully with the extended reflection model relxillD, which allows for higher densities than the standard relxill model. This returns a disc electron density n e > 10 18.7 cm −3 and lowers the iron abundance from Z_Fe = 24^+3_-4 Z_ with n e ≡ 10 15 cm −3 to Z_Fe = 6.6^+0.8_-2.1 Z_ .